Pertimbangan Anestesi Preoperatif, Intraoperatif dan Pascaoperatif pada Pasien Geriatri: Literature Review - Putri Puspa Devi; Khadafi Indrawan (CV. Jasa Sukses Abadi, 2026)
Geriatric patients commonly experience multiple anatomical and physiological changes related to the aging process, involving the cardiovascular, respiratory, metabolic, endocrine, digestive, nervous, and musculoskeletal systems. These changes increase perioperative risks associated with anesthesia and contribute to higher morbidity and mortality rates. This literature review aims to minimize undesirable events and complications that may occur during the preoperative, intraoperative, and postoperative phases in geriatric patients. The method used involved a literature search of studies published between 2015 and 2025 using the NCBI, PubMed, and Google Scholar databases, focusing on anesthetic considerations in geriatric patients across perioperative phases. Selected articles were analyzed using a systematic literature review approach, including data collection, evaluation, and synthesis in accordance with the review objectives. The findings indicate that preoperative preparation in elderly patients should include comprehensive functional assessment to identify cognitive impairment, reduced cardiopulmonary reserve, depression, frailty, nutritional status, polypharmacy, and anticoagulation issues. Intraoperative management involves appropriate selection of anesthetic techniques and pharmacological agents, close monitoring, careful fluid or intravenous transfusion management, adequate pulmonary ventilation, and prevention of hypothermia. Postoperative considerations include effective perioperative analgesia, prevention and early detection of postoperative delirium and cognitive dysfunction, as well as monitoring for other potential complications. A comprehensive and integrated anesthetic approach is essential to improve patient safety and optimize clinical outcomes in the geriatric population undergoing surgical procedures.